Cytotoxic aporphine alkaloids from leaves and twigs of pseuduvaria trimera (Craib) - Wuttikrai Sesang (2018)
From ethyl acetate-methanol extracts of leaves and twigs of Pseuduvaria trimera a new aporphine alkaloid; 8-hydroxy-1,4,5- Trimethoxy-7-oxoaporphine or 8-hydroxyartabonatine C (1) was isolated, together with the known 1,2,3- Trimethoxy-4,5- dioxo-6a,7-dehydroaporphine (ouregidione, 2). Their structures were elucidated by a combination of spectral methods; mainly 2D NMR; IR and MS. Compounds 1 and 2 exhibited cytotoxic activity with IC50values of 26.36 ± 5.18 μM and 12.88 ± 2.49 μM, respectively, for human hepatocellular carcinoma HepG2 cells, and 64.75 ± 4.45 and 67.06 ± 3.5 μM, respectively, for human breast cancer MDA-MB231 cells. Both compounds displayed anti-cancer activity but less than that of doxorubicin; a conventional chemotherapeutic drug, the IC50levels of which were 2.21 ± 1.72 and 1.83 ± 0.09 μM for HepG2 and MDA-MB231 cells, respectively.